1987
DOI: 10.1113/jphysiol.1987.sp016880
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory amino acid receptor‐mediated transmission of somatosensory evoked potentials in the rat thalamus.

Abstract: SUMMARY1. To examine the role of excitatory amino acid receptors in the rat ventrobasal thalamic nucleus (v.b.t.n.) for the transmission of cortical somatosensory evoked potentials (s.e.p.s), potentials were recorded from the somatosensory cortex of barbiturate-anaesthetized and of unanaesthetized awake rats. The effects of microapplications of the selective N-methyl-D-aspartate (NMDA) antagonist (-)-2-amino-7-phosphono-heptanoate ((-)AP7) and the broad-spectrum excitatory amino acid antagonist 1-(p-chloroben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…b) we demonstrated that terminals of lamina I axons in the nucleus submedius are involved in complex synaptic aggregations with pre-and postsynaptic dendrites, similar to the organization of lemniscal afferent terminals and intrinsic neuronal components in the ventrobasal complex (Blomqvist et al, 1985;Ralston et al, 1988). Recent immunocytochemical studies (De Biasi and Rustioni, 1990;Broman and Ottersen, 1992) have shown enrichment of glutamate-like immunoreactivity (Glu-LI) in terminals of ascending somatosensory afferent fibres in the ventrobasal complex, corroborating pharmacological evidence that excitatory amino acids (EAA) mediate transmission between lemniscal terminals and thalamic neurons (Salt, 1986;Klockgether, 1987;Salt and Eaton, 1991). However, it is not known whether TSTT fibres, carrying nociceptivespecific information to the thalamus, also use glutamate as a neurotransmitter.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…b) we demonstrated that terminals of lamina I axons in the nucleus submedius are involved in complex synaptic aggregations with pre-and postsynaptic dendrites, similar to the organization of lemniscal afferent terminals and intrinsic neuronal components in the ventrobasal complex (Blomqvist et al, 1985;Ralston et al, 1988). Recent immunocytochemical studies (De Biasi and Rustioni, 1990;Broman and Ottersen, 1992) have shown enrichment of glutamate-like immunoreactivity (Glu-LI) in terminals of ascending somatosensory afferent fibres in the ventrobasal complex, corroborating pharmacological evidence that excitatory amino acids (EAA) mediate transmission between lemniscal terminals and thalamic neurons (Salt, 1986;Klockgether, 1987;Salt and Eaton, 1991). However, it is not known whether TSTT fibres, carrying nociceptivespecific information to the thalamus, also use glutamate as a neurotransmitter.…”
Section: Introductionmentioning
confidence: 89%
“…Although a high level of Glu-LI is probably a distinctive feature of glutamatergic terminals in the central nervous system, immunogold findings must be evaluated in conjunction with other types of data on EAA neurotransmission. With respect to the ventrobasal complex, there is abundant pharmacological evidence that supports the involvement of EAAs in the transmission from ascending somatosensory afferent fibres (Salt, 1986;Klockgether, 1987: Salt and Eaton, 1989.…”
Section: Glutamate As a Putative Neurotransmitter In The Nucleus Submmentioning
confidence: 99%
“…Negative findings with this technique do not, however, rule out a transmitter role for Glu or other excitatory amino acids, as the sensitivity for detection may vary between different putative glutamatergic pathways (for reviews, see Storm-Mathisen and Ottersen, 1988;Ottersen, 199 1). Electrophysiologiopharmacologic studies in rats have recently provided increasing evidence for an involvement of excitatory amino acids in the synaptic transmission between ascending somatosensory afferents and neurons in the thalamic ventrobasal complex (Salt, 1986(Salt, ,1988Klockgether, 1987), and the response to somatosensory stimulation in the ventrobasal complex' seems to involve both NMDA and non-NMDA receptors Eaton, 1989, 1991). The present findings that Glu-LI is enriched both in peroxidase-positive CTT terminals and non-peroxidase-labeled RL terminals further support the existence of excitatory amino acid neurotransmission between these afferents and VPL neurons and strongly suggest that Glu is an endogenous agonist for the receptors.…”
Section: General Comments On Glutamate Immunohistochemistrymentioning
confidence: 99%
“…That GABA is a neurotransmitter in VPL local circuit neurons and in reticular thalamic neurons projecting to the VPL has been well established, and there is strong evidence for excitatory amino acids, foremost glutamate (Glu), as neurotransmitters in the cortical projection to the VPL (Jones, 1985;Rustioni and Weinberg, 1989). However, electrophysiologic-pharmacologic studies have during recent years suggested that excitatory amino acids may also be involved in synaptic transmission between somatosensory afferents and thalamic neurons (Salt, 1986(Salt, , 1988Klockgether, 1987;Salt and Eaton, 1989). Immunohistochemical studies have also revealed the presence of glutamate-like immunoreactivity (Glu-LI) in lemniscal-type terminals in the VPL Spreafico et al, 1989;De Biasi and Rustioni, 1990).…”
mentioning
confidence: 99%
“…Several lines of evidence concur in suggesting that the excitatory amino acid glutamate (Glu) is an important transmitter in VP Rustioni and Weinberg, 1989): excitatory effects of Glu on VP neurons were reported in physiological studies (Hicks et al, 1986;Salt, 1986Salt, , 1987Klockgether, 1987;Salt and Eaton, 1989;Eaton and Salt, 1990) and Glu binding sites and receptors were shown in VP (Monaghan and Cotman, 1985;Cotman et al, 1987;Petralia and Wenthold, 1992;Frassoni et al, 1993). In particular, the demonstration that receptors for Glu are involved in the responses of VP neurons to stimulation of somatosensory afferents (Salt, 1986(Salt, , 1987Salt and Eaton, 1989) suggests that this excitatory amino acid functions as the transmitter mediating the responses of VP neurons to stimulation of second order sensory afferents.…”
mentioning
confidence: 94%